A sensitive flow injection chemiluminescence method for the determination of progesterone. Issue 4 (14th June 2011) - Cao, Wei; Gong, Pixue; Liu, Wenwen; Zhuang, Mei; Yang, Jinghe
<x xml:space="preserve">Abstract</x> A sensitive flow injection (FI) chemiluminescence (CL) method was developed for the determination of trace amounts of progesterone. This method was based on the luminescent properties of the tris(1, 10‐phenanthroline) ruthenium(II) ‐ potassium permanganate (KMnO4) ‐ progesterone in acidic medium sensitized by Na2SO3. With the peak height as a quantitative parameter applying optimum conditions, the relative CL intensity was linear with progesterone concentration in the range of 1.0 × 10−10 ∼ 6.0 × 10−9 g·ml−1 and 6.0 × 10−9 ∼ 4.0 × 10−8 g·ml−1 with a detection limit of 7.1 × 10−11 g·ml−1. The relative standard deviation (RSD) was 2.79% for 1.0 × 10−8 g·ml−1 progesterone (n = 11). The proposed method held low detection limit and was successfully applied to determination of progesterone in pharmaceutical preparations. The possible CL reaction mechanism was also discussed. Copyright © 2011 John Wiley & Sons, Ltd.